Diagnosis of a Bleeding Dieulafoy Lesion on Computed Tomography and Its Subsequent Embolization - Robert M Penner; Richard J Owen; C Noel Williams (Canadian Journal of Gastroenterology)
Dieulafoy lesions are a potentially serious cause of gastrointestinal bleeding. Because they may bleed intermittently, and only be endoscopically evident during hemorrhage, their diagnosis can be challenging. This is the first case to be reported in the English literature of a patient with a Dieulafoy lesion diagnosed during computed tomography (CT) examination. Reduced acquisition times required for multislice helical CT allow the application of CT angiography in the diagnosis of gastrointestinal bleeding. CT scans are now widely used in the diagnostic algorithm for acute gastrointestinal hemorrhage, and the present case illustrates that with fortuitous timing, they can provide critical information and an opportunity for selected angiography and coil embolization.